Landscape for a planet with two dwarf suns. Issue 3 (1st September 2016) - Treib, Marc
Abstract: C.H.Z. (Continually Habitable Zones) is an astrogeological term for planets that may be able to support life similar to that on earth. It is also the title of a 2011 film by French artist Philippe Parreno, created using a site designed, reshaped, and planted by Belgian landscape architect Bas Smets. Imagined as the product of a hyper-photosynthesis produced by the pair of dwarf suns, Smets cast the C.H.Z. landscape as dark, approaching black. This essay traces the planning and implementation of the site outside Porto, Portugal, the conception and making of the film, and what has happened to the site in the three years since filming. These are set against a broader discussion of landscape in relation to cinema.